Sebuah Kasus Lucio Phenomenon yang Fatal pada Pasien Lucio’s Leprosy - Puspitasari, Galuh; Yuniaswan, Anggun; Ekasari, Dhany (Jurnal Klinik dan Riset Kesehatan, 2022)
The diagnosis of Lucio's leprosy is difficult because cutaneous manifestations are often atypical. Patients often come in severe conditions accompanied by Lucio phenomenon. A 33 years old man had a major complaint of purplish blue spots and ulcers accompanied by blisters for the past four days. The patient's eyebrows and eyelashes have been lost for the past year, but there were no prior histories of painless skin lesions and nerve impairment. Dermatological examination showed multiple stellate purpuric patches scattered almost throughout the body. There were also numerous bullas and erosions covered by dark necrotic areas, mainly on extremities. These involved about 40% of his Body Surface Area (BSA). The slit skin smears revealed BI 6+ and MI 1%. Hematoxylin and Eosin histopathology examination revealed a granulomatous inflammatory reaction accompanied by vasculitis. While Ziehl Neelsen's staining revealed abundant acid-fast bacilli scattered in the dermis area, some infiltrated vascular endothelial walls supported a Lucio phenomenon. The patient also had severe anemia, neutrophilia, hyperkalemia, and hypoalbuminemia. The extent of skin lesions and septic conditions complicate the management and lead to high levels of morbidity and mortality. Lucio's phenomenon is a severe leprosy reaction that is difficult to recognize with necrotizing erythematous cutaneous lesions as characteristic clinical manifestations, especially on the extremities. Extensive involvement of the lesion and sepsis were the main obstacles that were encountered during this case management. The administration of multidrug therapy for multibacillary leprosy (MDT-MB) WHO regimens are the primary therapy that can be combined with systemic corticosteroids.